A bifunctional catalyst for electrochemical hydrogen evolution reaction and urea electrocatalytic oxidation reaction and its preparation method and application

The nickel-based molybdenum oxide catalyst is supported by nickel-based molybdenum oxide catalyst, and the problems of high energy consumption and high cost of precious metal catalysts in electrolyzed hydrogen production and urea electrocatalytic oxidation reaction are solved, and low-cost, efficient and stable catalytic effect is achieved, suitable for hydrogen energy Industrial application.

CN115896802BActive Publication Date: 2024-12-17ZHEJIANG SCI-TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211319259.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-26
Publication Date
2024-12-17
Estimated Expiration
2042-10-26

AI Technical Summary

Technical Problem

The existing electrolytic hydrogen production process requires a high overpotential, high energy consumption and low Faraday efficiency, slow kinetics of urea electrocatalytic oxidation reaction, traditional precious metal catalysts have high cost, low reserves and poor long-term stability, making it difficult to achieve large-scale industrialization application.

Method used

Develop a bifunctional catalyst with nickel-based supported nickel-molybdenum oxide, containing Mo-O-Ni bonds, with divalent and high-valent molybdenum, which can efficiently catalyze electrochemical hydrogen evolution and urea electrocatalytic oxidation reactions in alkaline solutions, replacing precious metals The catalyst is prepared by hydrothermal calcining method and is suitable for electrolyzing urea and seawater hydrogen production.

Benefits of technology

It has achieved low-cost, high-efficiency, low-energy consumption and stable electrochemical hydrogen evolution and urea electrocatalytic oxidation reactions, which are suitable for the green preparation of hydrogen energy and urea pollution treatment, and is suitable for large-scale industrial applications and promote the development of the hydrogen energy industry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115896802B_ABST
    Figure CN115896802B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of electrocatalysis technology, and discloses a bifunctional catalyst for electrochemical hydrogen evolution reaction and urea electrocatalytic oxidation reaction, and a preparation method and application thereof. The bifunctional catalyst comprises a nickel substrate and a nickel-molybdenum oxide active material loaded on the nickel substrate, wherein the nickel-molybdenum oxide contains a Mo-O-Ni bond, divalent nickel, and tetravalent molybdenum and / or hexavalent molybdenum. The preparation method of the bifunctional catalyst comprises the following steps: (1) immersing the nickel substrate in an ammonium molybdate solution, performing a hydrothermal reaction, separating the product, and obtaining a precursor; (2) calcining the precursor to obtain a bifunctional catalyst. The bifunctional catalyst of the present invention can efficiently and stably catalyze the electrochemical hydrogen evolution reaction and the electrocatalytic oxidation reaction of urea, and does not require the use of precious metals, has low cost, and has a simple preparation method, and has good application prospects in hydrogen production and urea pollution treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrocatalysis technology, and in particular to a bifunctional catalyst for electrochemical hydrogen evolution reaction and urea electrocatalytic oxidation reaction, and a preparation method and application thereof. Background Art

[0002] As a clean secondary energy source, hydrogen energy is safe, environmentally friendly and sustainable compared to traditional fossil energy, and has high energy density and combustion calorific value. It is an important research direction for clean energy. Hydrogen production by water electrolysis is one of the common methods for preparing hydrogen. It includes two half reactions: the electrochemical hydrogen evolution reaction (HER) at the cathode and the electrochemical oxygen evolution reaction (OER) at the anode. Due to the slow kinetic process of OER, a high overpotential is often required to produce hydrogen during water electrolysis, resulting in serious energy consumption and low Faraday efficiency.

[0003] Urea is an ideal hydrogen storage material, and the urea electrocatalytic oxidation reaction (UOR) can use urea to produce hydrogen. The theoretical potential of UOR is 0.37V, which is lower than that of OER (the theoretical potential of OER is 1.23V). Therefore, using UOR instead of or in conjunction with OER to produce hydrogen can greatly reduce energy consumption. However, UOR involves a complex six-electron transfer process and a complex gas evolution reaction, so its kinetic process is still relatively slow and requires the use of catalysts to accelerate its reaction. Traditional precious metal catalysts (such as platinum-based catalysts, iridium-based catalysts, and ruthenium-based catalysts) can effectively reduce the UOR reaction energy barrier and accelerate the reaction rate, but these precious metal catalysts have the disadvantages of high cost, low reserves, and poor long-term operating stability, making it difficult to achieve large-scale industrial applications. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a bifunctional catalyst for electrochemical hydrogen evolution reaction and urea electrocatalytic oxidation reaction, and a preparation method and application thereof. The bifunctional catalyst of the present invention can efficiently and stably catalyze the electrochemical hydrogen evolution reaction and the urea electrocatalytic oxidation reaction, and does not require the use of precious metals, has low cost, and is simple in preparation method, and has good application prospects in hydrogen production and urea pollution treatment.

[0005] The specific technical scheme of the present invention is:

[0006] First, the present invention provides a bifunctional catalyst for electrochemical hydrogen evolution reaction and urea electrocatalytic oxidation reaction, including a nickel substrate and a nickel-molybdenum oxide active supported on the nickel substrate; the nickel-molybdenum oxide contains a Mo-O-Ni bond; the nickel-molybdenum oxide contains divalent nickel, and also contains tetravalent molybdenum and / or hexavalent molybdenum.

[0007] The bifunctional catalyst of the present invention can effectively catalyze the electrochemical hydrogen evolution reaction (HER) and the urea electrocatalytic oxidation reaction (UOR), and the active component is molybdenum nickel oxide, which does not require the use of precious metals, and can solve the problems of high cost, low reserves and poor long-term stability of precious metal catalysts. The mechanism of this bifunctional catalyst catalyzing HER and UOR is as follows: During the electrochemical oxidation process, Ni 2+ Capable of in-situ generation of Ni 3+ , which is the active site that contributes to the high activity of HER and UOR; while high-valent molybdenum (Mo 4+ and / or Mo 6+ ) can make you 2+ More easily oxidized to Ni 3+ , increasing the active sites in the catalyst, thereby promoting the HER and UOR processes.

[0008] The bifunctional catalyst of the present invention can be used to produce hydrogen by electrolyzing urea in alkaline solution, and can also be used to produce hydrogen by electrolyzing seawater, and has the advantages of high efficiency, low energy consumption and stability. According to the test, the bifunctional catalyst has a current density of 10mA / cm2 and a current density of 1.383V (the theoretical voltage required for urea oxidation reaction). 2 The invention shows excellent urea oxidation performance. When an alkaline solution containing 0.5M urea is used as the electrolyte, the overpotential of the urea oxidation reaction is 133mV. The invention also shows high activity for the hydrogen evolution reaction, and the overpotential in the hydrogen evolution reaction is -183mV. Moreover, the hydrogen production device constructed by using the bifunctional catalyst of the invention has better overall hydrolysis performance in urea alkaline solution than the noble metal catalyst, and can operate stably for a long time. 2 The reaction time was 30 hours at a current density of 100 mA / cm 2 When urea is oxidized, the starting potential of the bifunctional catalyst of the present invention is 1.744 V, which is 176 mV earlier than that of the electrolysis of alkaline solution.

[0009] In summary, the bifunctional catalyst of the present invention can stably catalyze the electrochemical hydrogen evolution reaction and the urea electrocatalytic oxidation reaction at low cost, high efficiency, and low energy consumption, and therefore has broad application scenarios in the green preparation of hydrogen energy and fuel cells, can achieve efficient and stable hydrogen production and urea pollution treatment, and is suitable for large-scale industrial electrochemical hydrogen production, and can play a positive role in promoting the development of the hydrogen energy industry.

[0010] Preferably, trivalent nickel is also present in the nickel-molybdenum oxide.

[0011] Preferably, the nickel substrate is a nickel sheet, a nickel mesh or nickel foam, and more preferably nickel foam.

[0012] Second, the present invention provides a method for preparing the bifunctional catalyst, comprising the following steps:

[0013] (1) Immersing the nickel substrate in an ammonium molybdate solution to perform a hydrothermal reaction, separating the product, and obtaining a precursor;

[0014] (2) Calcinate the precursor to obtain a bifunctional catalyst.

[0015] The present invention adopts a hydrothermal and calcination two-step method to load molybdenum nickel oxide on a nickel substrate. The specific process is as follows: during the hydrothermal reaction, ammonium molybdate reacts with the nickel substrate under high temperature and high pressure to generate a nickel-molybdenum hydroxide precursor, and the XRD of the uncalcined precursor is amorphous; then calcined to form nickel-molybdenum oxide, the crystallinity of the calcined catalyst is improved, the XRD standard card corresponds to MoO2, and the three strong peaks of the nickel substrate, the nickel substrate in-situ precipitates Ni and combines with MoO2, and molybdenum nickel oxide is loaded on the nickel substrate, and the nickel-molybdenum oxide has a good promoting effect on HER and UOR. The hydrothermal calcination method of the present invention is simple in process and has a wide range of application, and can meet the needs of large-scale industrial production.

[0016] Preferably, before step (1), the nickel substrate is pretreated to remove nickel oxide on the surface.

[0017] Preferably, the specific process of the pretreatment includes the following steps: immersing the nickel substrate in a 2-5 mol / L hydrochloric acid aqueous solution, ultrasonically treating it for 10-20 min, and then ultrasonically treating it in a mixed solution of acetone and ethanol for 2-4 times by the same operation.

[0018] Preferably, in step (1), the temperature of the hydrothermal reaction is 100-120°C for 5-7h, more preferably 120°C.

[0019] When the temperature of the hydrothermal reaction is low, the bonding strength between the molybdenum nickel oxide and the nickel substrate in the obtained bifunctional catalyst is low, which will cause the catalyst to have relatively poor stability; and when the temperature of the hydrothermal reaction is high, the generated nickel-molybdenum precursor is easy to agglomerate and fall off from the nickel substrate, resulting in reduced stability of the synthesized nickel-molybdenum precursor, resulting in relatively poor catalytic activity. Therefore, the hydrothermal reaction temperature in the present invention is preferably 100-120°C, within which temperature range, higher catalyst stability and catalytic activity can be achieved.

[0020] Preferably, in step (1), the concentration of the ammonium molybdate solution is 0.013-0.017 g / mL, more preferably 0.017 g / mL.

[0021] As the concentration of ammonium molybdate solution increases, the amount of nickel-molybdenum oxide generated increases, which is beneficial to the adsorption of urea molecules and promotes the Ni 2+ In situ generation of Ni during electrochemical oxidation 3+, thereby improving the catalytic activity of the bifunctional catalyst. However, when the concentration of the ammonium molybdate solution is too high, the adsorption of urea by the catalyst is too strong, and the generated intermediate product is difficult to desorb, which will cause the catalytic activity to decrease. Therefore, the concentration of the ammonium molybdate solution in the present invention is preferably 0.013-0.017, within which a higher catalytic activity can be achieved.

[0022] Preferably, in step (2), the calcination temperature is 300-500°C, more preferably 400°C.

[0023] When the calcination temperature is low, molybdenum-nickel oxide is not completely formed on the catalyst surface, which will cause the catalytic performance of the bifunctional catalyst to be relatively poor; when the calcination temperature is high, the porous nanosheet network structure on the surface of the bifunctional catalyst is easily destroyed, the porous structure of the catalyst is easy to collapse at high temperature, and the surface of the nickel substrate becomes brittle after calcination at high temperature, which will also have an adverse effect on its catalytic performance. Therefore, the calcination temperature in the present invention is preferably 300-500°C, within which temperature range, higher catalytic activity can be achieved.

[0024] Preferably, in step (2), the calcination time is 1.5-2.5 hours.

[0025] Preferably, in step (2), the calcination is carried out in a nitrogen atmosphere.

[0026] Calcination in a nitrogen atmosphere is conducive to the synthesis of nickel-molybdenum oxides, and the catalyst is more likely to form oxygen vacancies, have more active sites and faster charge transfer kinetics, so that the obtained bifunctional catalyst has better catalytic performance. When calcination is carried out in an atmosphere containing oxygen or hydrogen, there are fewer oxygen vacancies and active sites on the catalyst surface, resulting in poor catalyst performance.

[0027] Thirdly, the present invention provides the use of the bifunctional catalyst in an electrochemical hydrogen evolution reaction or a urea electrocatalytic oxidation reaction.

[0028] Preferably, the application comprises the following steps: using the bifunctional catalyst as a working electrode to form a three-electrode system with a counter electrode and a reference electrode to perform an electrochemical hydrogen evolution reaction or a urea electrocatalytic oxidation reaction.

[0029] Compared with the prior art, the present invention has the following advantages:

[0030] (1) The bifunctional catalyst of the present invention can stably catalyze the electrochemical hydrogen evolution reaction and the urea electrocatalytic oxidation reaction at low cost, high efficiency, low energy consumption, and has a simple preparation process, and has good application prospects in hydrogen production and urea pollution treatment;

[0031] (2) In the preparation process of the bifunctional catalyst of the present invention, by controlling the hydrothermal reaction temperature, calcination temperature and calcination atmosphere, the obtained bifunctional catalyst can have good catalytic activity and stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 These are the OER and UOR polarization curves of the bifunctional catalyst at different ammonium molybdate contents in Test Example 1.

[0033] Figure 2 These are the OER and UOR polarization curves of the bifunctional catalyst at different calcination temperatures in Test Example 2.

[0034] Figure 3 These are the OER and UOR polarization curves of the bifunctional catalyst calcined under different atmospheres in Test Example 3.

[0035] Figure 4 These are the OER and UOR polarization curves of the bifunctional catalyst before and after calcination in Test Example 4.

[0036] Figure 5 These are the OER and UOR polarization curves of the bifunctional catalyst at different hydrothermal temperatures in Test Example 5.

[0037] Figure 6 This is the UOR polarization curve diagram under different urea concentrations in Test Example 6.

[0038] Figure 7 HER polarization curves of different catalysts in Test Example 7.

[0039] Figure 8 The UOR polarization curve, Tafel slope, impedance, and electrochemical active surface area curve of different catalysts in Test Example 8 are shown in FIG. Figure 8 (A) Performance diagram of UOR and OER of different catalysts; Figure 8 (B) Tafel slope plot of different catalysts; Figure 8 (C) Impedance diagram of different catalysts; Figure 8 (D) Electrochemically active surface area diagram of different catalysts.

[0040] Fig. 9 This is the UOR polarization curve of urea alkali solution and seawater in Test Example 9.

[0041] Fig.10 This is a polarization curve diagram of the two-electrode urea-assisted water electrolysis in Test Example 10. Among them, Fig.10 (A) Polarization curves of water electrolysis with and without urea assistance; Fig.10 (B) Polarization curves of water electrolysis of MoO2-Ni / NF catalyst and precious metal catalyst.

[0042] Fig.11 This is a graph of hydrogen production and Faraday efficiency in two-electrode urea-assisted water electrolysis in Test Example 11. Fig.11 (A) is the hydrogen production of the two electrodes; Fig.11 (B) is the Faraday efficiency diagram of the two electrodes.

[0043] Fig.12 This is the current-time diagram of the two-electrode urea-assisted water electrolysis in Test Example 12.

[0044] Fig.13 This is the in-situ infrared spectrum of the bifunctional catalyst in Test Example 13 in the UOR test.

[0045] Fig.14 The OER and UOR polarization curves of the bifunctional catalyst with and without an external nickel source in Test Example 14.

[0046] Fig.15 These are the OER and UOR polarization curves of the bifunctional catalysts on different substrates in Test Example 15.

[0047] Fig.16 This is the XRD pattern of the bifunctional catalyst in Test Example 16 (1).

[0048] Fig.17 This is the XPS graph of the bifunctional catalyst before and after the electrochemical UOR performance test in Test Example 16 (2). Fig.17 (A) is the full spectrum before and after the test; Fig.17 (B) is the spectrum of Ni before and after the test; Fig.17 (C) is the spectrum of Mo before and after the test; Fig.17 (D) is the spectrum of O before and after the test.

[0049] Fig.18 The Raman spectra of the precursor and the bifunctional catalyst in Test Example 16 (3) are shown. DETAILED DESCRIPTION

[0050] The present invention will be further described below in conjunction with the embodiments.

[0051] The following examples can enable professionals in this field to more fully understand the present invention, but do not limit the present invention in any way.

[0052] A bifunctional catalyst for electrochemical hydrogen evolution reaction and urea electrocatalytic oxidation reaction, comprising a nickel substrate and a nickel-molybdenum oxide active material supported on the nickel substrate; the nickel-molybdenum oxide contains a Mo-O-Ni bond; the nickel-molybdenum oxide contains divalent nickel or divalent nickel and trivalent nickel, and also contains tetravalent molybdenum and / or hexavalent molybdenum.

[0053] Optionally, the nickel substrate is a nickel sheet, a nickel mesh or nickel foam.

[0054] A method for preparing the bifunctional catalyst comprises the following steps:

[0055] (1) pre-treating the nickel substrate to remove nickel oxide on the surface to obtain a pre-treated nickel substrate;

[0056] (2) immersing the pretreated nickel substrate in an ammonium molybdate solution to perform a hydrothermal reaction, separating the product, and obtaining a precursor;

[0057] (3) Calcinate the precursor to obtain a bifunctional catalyst.

[0058] Optionally, the specific process of the pretreatment includes the following steps: immersing the nickel substrate in a 2-5 mol / L hydrochloric acid aqueous solution, ultrasonically treating it for 10-20 minutes, and then ultrasonically treating it in a mixed solution of acetone and ethanol for 2-4 times by the same operation.

[0059] Optionally, in step (1), the temperature of the hydrothermal reaction is 100-120° C. and the time is 5-7 h.

[0060] Optionally, in step (1), the concentration of the ammonium molybdate solution is 0.013-0.017 g / mL.

[0061] Optionally, in step (2), the calcination temperature is 300-500° C. and the calcination time is 1.5-2.5 h.

[0062] Optionally, in step (2), the calcination is carried out in a nitrogen atmosphere.

[0063] The application of the bifunctional catalyst in an electrochemical hydrogen evolution reaction or an electrocatalytic oxidation reaction of urea comprises the following steps: using the bifunctional catalyst as a working electrode to form a three-electrode system with a counter electrode and a reference electrode to perform an electrochemical hydrogen evolution reaction or an electrocatalytic oxidation reaction of urea.

[0064] Example 1

[0065] The bifunctional catalyst for electrochemical hydrogen evolution reaction and urea electrocatalytic oxidation reaction was prepared by the following steps:

[0066] First, immerse the 2cm×2cm nickel foam in 2mol / L HCL for 10min, and then perform ultrasonic treatment three times in a mixed solution of acetone and ethanol in the same way to remove the oxide on the surface. Take out the nickel foam, rinse it with deionized water, and put it in a 60℃ oven to dry for 12h to remove moisture. After the end, take 0.3g of ammonium molybdate and dissolve it in 30mL water, stir it evenly, add the nickel foam and stir it for 10min, pour the mixture of nickel foam and ammonium molybdate solution into the hydrothermal reactor, hydrothermal it at 120℃ for 6h to obtain the precursor, rinse it with ethanol and water, and dry it for use. After the end, put the precursor into a quartz boat and put it in the center of the temperature zone of the tube furnace for calcination, with inert gas N2 as the protective gas. Set the temperature of the tube furnace at 400℃ for 2h to obtain a bifunctional catalyst (denoted as MoO2-Ni / NF).

[0067] Example 2

[0068] First, immerse the 2cm×2cm nickel foam in 2mol / L HCL for 10min, and then perform ultrasonic treatment three times in a mixed solution of acetone and ethanol in the same way to remove the oxide on the surface. Take out the nickel foam, rinse it with deionized water, and put it in a 60℃ oven to dry for 12h to remove moisture. After the end, take 0.4g of ammonium molybdate and dissolve it in 30mL water, stir it evenly, add the nickel foam and stir it for 10min, pour the mixture of nickel foam and ammonium molybdate solution into the hydrothermal reactor, hydrothermal it at 120℃ for 6h to obtain the precursor, rinse it with ethanol and water, and dry it for use. After the end, put the precursor into a quartz boat and put it in the center of the temperature zone of the tube furnace for calcination, with inert gas N2 as the protective gas. Set the temperature of the tube furnace at 400℃ for 2h to obtain a bifunctional catalyst (recorded as MoO2-Ni / NF).

[0069] Example 3

[0070] First, immerse the 2cm×2cm nickel foam in 2mol / L HCL for 10min, and then perform ultrasonic treatment three times in a mixed solution of acetone and ethanol in the same way to remove the oxide on the surface. Take out the nickel foam, rinse it with deionized water, and put it in a 60℃ oven to dry for 12h to remove moisture. After the end, take 0.5g of ammonium molybdate and dissolve it in 30mL water, stir it evenly, add the nickel foam and stir it for 10min, pour the mixture of nickel foam and ammonium molybdate solution into the hydrothermal reactor, hydrothermal it at 120℃ for 6h to obtain the precursor, rinse it with ethanol and water, and dry it for use. After the end, put the precursor into a quartz boat and put it in the center of the temperature zone of the tube furnace for calcination, with inert gas N2 as the protective gas. Set the temperature of the tube furnace at 400℃ for 2h to obtain a bifunctional catalyst (recorded as MoO2-Ni / NF).

[0071] Example 4

[0072] First, immerse the 2cm×2cm nickel foam in 2mol / L HCL for 10min, and then perform ultrasonic treatment three times in a mixed solution of acetone and ethanol in the same way to remove the oxide on the surface. Take out the nickel foam, rinse it with deionized water, and put it in a 60℃ oven to dry for 12h to remove moisture. After that, take 1g of ammonium molybdate and dissolve it in 30mL water, stir it evenly, add the nickel foam and stir it for 10min, pour the mixture of nickel foam and ammonium molybdate solution into the hydrothermal reactor, hydrothermal it at 120℃ for 6h to obtain the precursor, rinse it with ethanol and water, and dry it for use. After that, put the precursor into a quartz boat and put it in the center of the temperature zone of the tube furnace for calcination, with inert gas N2 as the protective gas. Set the temperature of the tube furnace at 400℃ for 2h to obtain a bifunctional catalyst (denoted as MoO2-Ni / NF).

[0073] Example 5

[0074] First, immerse the 2cm×2cm nickel foam in 2mol / L HCL for 10min, and then perform ultrasonic treatment three times in a mixed solution of acetone and ethanol in the same way to remove the oxide on the surface. Take out the nickel foam, rinse it with deionized water, and put it in a 60℃ oven to dry for 12h to remove moisture. After the end, take 0.5g of ammonium molybdate and dissolve it in 30mL water, stir it evenly, add the nickel foam and stir it for 10min, pour the mixture of nickel foam and ammonium molybdate solution into the hydrothermal reactor, hydrothermal it at 120℃ for 6h to obtain the precursor, rinse it with ethanol and water, and dry it for use. After the end, put the precursor into a quartz boat and put it in the center of the temperature zone of the tube furnace for calcination, with inert gas N2 as the protective gas. Set the temperature of the tube furnace at 300℃ for 2h to obtain a bifunctional catalyst (recorded as MoO2-Ni / NF).

[0075] Example 6

[0076] First, immerse the 2cm×2cm nickel foam in 2mol / L HCL for 10min, and then perform ultrasonic treatment three times in a mixed solution of acetone and ethanol in the same way to remove the oxide on the surface. Take out the nickel foam, rinse it with deionized water, and put it in a 60℃ oven to dry for 12h to remove moisture. After that, take 0.5g of ammonium molybdate and dissolve it in 30mL water, stir it evenly, add the nickel foam and stir it for 10min, pour the mixture of nickel foam and ammonium molybdate solution into the hydrothermal reactor, hydrothermal it at 120℃ for 6h to obtain the precursor, rinse it with ethanol and water, and dry it for use. After that, put the precursor into a quartz boat and put it in the center of the temperature zone of the tube furnace for calcination, with inert gas N2 as the protective gas. Set the temperature of the tube furnace at 500℃ for 2h to obtain a bifunctional catalyst (denoted as MoO2-Ni / NF).

[0077] Example 7

[0078] First, immerse the 2cm×2cm nickel foam in 2mol / L HCL for 10min, and then perform ultrasonic treatment three times in a mixed solution of acetone and ethanol in the same way to remove the oxide on the surface. Take out the nickel foam, rinse it with deionized water, and put it in a 60℃ oven to dry for 12h to remove moisture. After that, take 0.5g of ammonium molybdate and dissolve it in 30mL water, stir it evenly, add the nickel foam and stir it for 10min, pour the mixture of nickel foam and ammonium molybdate solution into the hydrothermal reactor, hydrothermal it at 120℃ for 6h to obtain the precursor, rinse it with ethanol and water, and dry it for use. After that, put the precursor into a quartz boat and put it in the center of the temperature zone of the tube furnace for calcination, using hydrogen and argon (volume ratio H2 / Ar=5% / 95%) as the protective gas. Set the temperature of the tube furnace at 400℃ for 2h to obtain a bifunctional catalyst (denoted as MoO2-Ni / NF).

[0079] Example 8

[0080] First, immerse the 2cm×2cm nickel foam in 2mol / L HCL for 10min, and then perform ultrasonic treatment three times in a mixed solution of acetone and ethanol in the same way to remove the oxide on the surface. Take out the nickel foam, rinse it with deionized water, and put it in a 60℃ oven to dry for 12h to remove moisture. After that, take 0.5g of ammonium molybdate and dissolve it in 30mL water, stir it evenly, add the nickel foam and stir it for 10min, pour the mixture of nickel foam and ammonium molybdate solution into the hydrothermal reactor, hydrothermal it at 120℃ for 6h to obtain the precursor, rinse it with ethanol and water, and dry it for use. After that, put the precursor into a quartz boat, put it in the center of the temperature zone of the tube furnace for calcination, and calcine it in air. Set the temperature of the tube furnace at 400℃ for 2h to obtain a bifunctional catalyst (recorded as MoO2-Ni / NF).

[0081] Example 9

[0082] First, immerse the 2cm×2cm nickel foam in 2mol / L HCL for 10min, and then perform ultrasonic treatment three times in a mixed solution of acetone and ethanol in the same way to remove the oxide on the surface. Take out the nickel foam, rinse it with deionized water, and put it in a 60℃ oven to dry for 12h to remove moisture. After the end, take 0.5g of ammonium molybdate and dissolve it in 30mL water, stir it evenly, add the nickel foam and stir it for 10min, pour the mixture of nickel foam and ammonium molybdate solution into the hydrothermal reactor, hydrothermal it at 80℃ for 6h to obtain the precursor, rinse it with ethanol and water, and dry it for use. After the end, put the precursor into a quartz boat and put it in the center of the temperature zone of the tube furnace for calcination, with inert gas N2 as the protective gas. Set the temperature of the tube furnace at 400℃ for 2h to obtain a bifunctional catalyst (recorded as MoO2-Ni / NF).

[0083] Example 10

[0084] First, immerse the 2cm×2cm nickel foam in 2mol / L HCL for 10min, and then perform ultrasonic treatment three times in a mixed solution of acetone and ethanol in the same way to remove the oxide on the surface. Take out the nickel foam, rinse it with deionized water, and put it in a 60℃ oven to dry for 12h to remove moisture. After the end, take 0.5g of ammonium molybdate and dissolve it in 30mL water, stir it evenly, add the nickel foam and stir it for 10min, pour the mixture of nickel foam and ammonium molybdate solution into the hydrothermal reactor, hydrothermal it at 100℃ for 6h to obtain the precursor, rinse it with ethanol and water, and dry it for use. After the end, put the precursor into a quartz boat and put it in the center of the temperature zone of the tube furnace for calcination, with inert gas N2 as the protective gas. Set the temperature of the tube furnace at 400℃ for 2h to obtain a bifunctional catalyst (recorded as MoO2-Ni / NF).

[0085] Embodiment 11

[0086] First, immerse the 2cm×2cm nickel foam in 2mol / L HCL for 10min, and then perform ultrasonic treatment three times in a mixed solution of acetone and ethanol in the same way to remove the oxide on the surface. Take out the nickel foam, rinse it with deionized water, and put it in a 60℃ oven to dry for 12h to remove moisture. After the end, take 0.5g of ammonium molybdate and dissolve it in 30mL water, stir it evenly, add the nickel foam and stir it for 10min, pour the mixture of nickel foam and ammonium molybdate solution into the hydrothermal reactor, hydrothermal it at 150℃ for 6h to obtain the precursor, rinse it with ethanol and water, and dry it for use. After the end, put the precursor into a quartz boat and put it in the center of the temperature zone of the tube furnace for calcination, with inert gas N2 as the protective gas. Set the temperature of the tube furnace at 400℃ for 2h to obtain a bifunctional catalyst (recorded as MoO2-Ni / NF).

[0087] Comparative Example 1

[0088] First, immerse the 2cm×2cm nickel foam in 2mol / L HCL for 10min, and then perform ultrasonic treatment three times in a mixed solution of acetone and ethanol in the same way to remove the oxide on the surface. Take out the nickel foam, rinse it with deionized water, and put it in a 60℃ oven to dry for 12h to remove moisture. After that, take 0.5g of ammonium molybdate and dissolve it in 30mL water, stir it evenly, add the nickel foam and stir it for 10min, pour the mixture of nickel foam and ammonium molybdate solution into a hydrothermal reactor, hydroheat it at 120℃ for 6h to obtain a precursor, rinse it with ethanol and water, and dry it to obtain a bifunctional catalyst.

[0089] Comparative Example 2

[0090] First, immerse the 2cm×2cm nickel foam in 2mol / L HCL for 10min, and then perform ultrasonic treatment three times in a mixed solution of acetone and ethanol in the same way to remove the oxide on the surface. Take out the nickel foam, rinse it with deionized water, and put it in a 60℃ oven to dry for 12h to remove moisture. Weigh 5mg of precious metal RuO2, add 50μL Nafion solution, 200μL isopropanol and 700μL deionized water, and ultrasonicate for 30min to form a uniform dispersion to obtain RuO2 dispersion. A small amount of RuO2 dispersion is evenly dripped on two pieces of treated nickel foam, dried, and a bifunctional catalyst (referred to as RuO2 / NF) is obtained.

[0091] Comparative Example 3

[0092] First, immerse the 2cm×2cm nickel foam in 2mol / L HCL for 10min, and then perform ultrasonic treatment three times in a mixed solution of acetone and ethanol in the same way to remove the oxide on the surface. Take out the nickel foam, rinse it with deionized water, and put it in a 60℃ oven to dry for 12h to remove moisture. Weigh 5mg of precious metal Pt / C powder, add 50μL Nafion solution, 200μL isopropanol and 700μL deionized water, and ultrasonicate for 30min to form a uniform dispersion to obtain Pt / C dispersion. A small amount of Pt / C dispersion is evenly dripped on two pieces of treated nickel foam, dried, and the catalyst (referred to as Pt / C / NF) is obtained.

[0093] Comparative Example 4

[0094] First, immerse the 2cm×2cm nickel foam in 2mol / L HCL for 10min, and then perform ultrasonic treatment three times in a mixed solution of acetone and ethanol in the same way to remove the oxide on the surface. Take out the nickel foam, rinse it with deionized water, and put it in a 60℃ oven to dry for 12h to remove moisture. After that, take 0.5g of ammonium molybdate and 0.5g of nickel nitrate and dissolve them in water, stir evenly, add the nickel foam and stir for 10min, pour the mixture of nickel foam and ammonium molybdate solution into the hydrothermal reactor, hydrothermal at 120℃ for 6h, obtain the catalyst precursor, rinse it with ethanol and water, and dry it for use. After that, put the precursor into a quartz boat, put it in the center of the temperature zone of the tubular furnace for calcination, and calcine it under protective gas nitrogen. Set the temperature of the tubular furnace at 400℃ for 2h to obtain a bifunctional catalyst.

[0095] Comparative Example 5

[0096] First, immerse a 2cm×2cm carbon cloth in 2mol / L HCL for 10min, and then perform ultrasonic treatment three times in a mixed solution of acetone and ethanol in the same way to remove the oxide on the surface. Take out the carbon cloth, rinse it with deionized water, and put it in a 60℃ oven to dry for 12h to remove moisture. After the end, take 0.5g of ammonium molybdate and dissolve it in 30mL water, stir it evenly, add the carbon cloth and stir it for 10min, pour the carbon cloth and the solution into the hydrothermal reactor, hydrothermal it at 120℃ for 6h, obtain the precursor catalyst, rinse it with ethanol and water, and dry it for use. After the end, put the precursor catalyst into a quartz boat, put it in the center of the temperature zone of the tubular furnace for calcination, and calcine it in air. Set the temperature of the tubular furnace at 400℃ for 2h to obtain a bifunctional catalyst.

[0097] Test Example 1

[0098] The MoO2-Ni / NF catalysts prepared in Examples 1-4 were subjected to electrochemical UOR and OER performance tests using a CHI-660E electrochemical workstation. The OER performance was tested in a 1.0M KOH solution, and the UOR performance was tested in a 0.5mol / L urea lye solution. Ag / AgCl was used as the reference electrode, the counter electrode was a carbon rod, and the bifunctional catalyst prepared in Examples 1-4 was used as the working electrode. The UOR polarization curves obtained with different ammonium molybdate contents (ammonium molybdate contents were 0.3, 0.4, 0.5, and 1 g, respectively) are shown in Figure 1. Figure 1 As shown in the figure, as the amount of ammonium molybdate increases from 0.3g to 0.5g, the performance of the catalyst for urea oxidation gradually increases, indicating that the increase in Mo content is conducive to the adsorption of urea molecules and promotes the urea oxidation process; when the amount of ammonium molybdate increases from 0.5g to 1g, the performance decreases, indicating that the Mo content is too much, the adsorption is too strong, and the generated intermediate products are difficult to desorb, which is not conducive to the urea oxidation reaction.

[0099] Test Example 2

[0100] The MoO2-Ni / NF catalysts prepared in Examples 3, 5 and 6 were subjected to electrochemical UOR and OER performance tests using a CHI-660E electrochemical workstation. The OER performance was tested in a 1.0M KOH solution, and the UOR performance was tested in a 0.5mol / L urea lye solution. Ag / AgCl was used as the reference electrode, the counter electrode was a carbon rod, and the bifunctional catalysts prepared in Examples 3, 5 and 6 were used as the working electrode. The polarization curves obtained at different nitrogen calcination temperatures (wherein the calcination temperatures were 300°C, 400°C, and 500°C, respectively) are shown in Figure 1. Figure 2 As shown. The poor performance of the catalyst after low-temperature calcination at 300°C is because molybdenum-nickel oxide is not completely formed on the catalyst surface. The poor performance of the catalyst after high-temperature calcination at 500°C is because the porous nanosheet network structure on the catalyst surface is destroyed. The porous structure of the catalyst is easy to collapse at high temperatures, and the surface of the foamed nickel substrate becomes brittle after calcination at high temperatures, which also has an adverse effect on its catalytic performance. The best performance is achieved at 400°C, and the porous nanosheet network structure on the catalyst surface is completely retained.

[0101] Test Example 3

[0102] The MoO2-Ni / NF catalysts prepared in Examples 3, 7 and 8 were subjected to electrochemical UOR and OER performance tests using a CHI-660E electrochemical workstation. The OER performance was tested in a 1.0M KOH solution, and the UOR performance was tested in a 0.5mol / L urea lye solution. Ag / AgCl was used as the reference electrode, the counter electrode was a carbon rod, and the bifunctional catalysts prepared in Examples 3, 7 and 8 were used as the working electrode. The polarization curves obtained under different atmospheres (wherein the atmospheres were N2, H2 / Ar2, and air, respectively) were as follows: Figure 3 As shown. Calcination in a nitrogen atmosphere is conducive to the synthesis of nickel-molybdenum oxides. The catalyst is more likely to form oxygen vacancies, have more active sites and faster charge transfer kinetics, so that the obtained bifunctional catalyst has better catalytic performance. When calcination is carried out in an atmosphere containing oxygen or hydrogen, there are fewer oxygen vacancies and active sites on the catalyst surface, resulting in poor catalyst performance.

[0103] Test Example 4

[0104] The MoO2-Ni / NF catalyst prepared in Example 3 and the catalyst prepared in Comparative Example 1 were subjected to electrochemical UOR and OER performance tests using a CHI-660E electrochemical workstation. The OER performance was tested in a 1.0M KOH solution, and the UOR performance was tested in a 0.5mol / L urea lye solution. Ag / AgCl was used as the reference electrode, the counter electrode was a carbon rod, and the catalysts prepared in Example 3 and Comparative Example 1 were used as the working electrode. The polarization curves of the nitrogen calcined and uncalcined precursors were obtained as shown in FIG. Figure 4 As shown. The uncalcined precursor is nickel-molybdenum hydroxide, and the corresponding XRD is amorphous, with only three strong peaks of nickel foam being visible. After nitrogen calcination, the crystallinity of the catalyst increases, forming nickel-molybdenum oxide. The XRD standard card corresponds to MoO2 and the three strong peaks of nickel foam. Ni is precipitated in situ from nickel foam and combined with MoO2, and molybdenum-nickel oxide is loaded on the nickel substrate, and nickel-molybdenum oxide has a good promoting effect on urea oxidation.

[0105] Test Example 5

[0106] Using a CHI-660E electrochemical workstation, the MoO2-Ni / NF catalysts prepared in Examples 3 and 9-11 were subjected to electrochemical UOR and OER performance tests. The OER performance was tested in a 1.0M KOH solution, and the UOR performance was tested in a 0.5mol / L urea lye solution. Ag / AgCl was used as the reference electrode, the counter electrode was a carbon rod, and the catalysts prepared in Examples 3 and 9-11 were used as the working electrode. The polarization curves of the catalysts prepared at different hydrothermal temperatures (wherein the hydrothermal temperatures were 80°C, 100°C, 120°C, and 150°C, respectively) were obtained as shown in FIG. Figure 5When the temperature of the hydrothermal reaction is low, the bonding strength between the molybdenum nickel oxide and the nickel substrate in the obtained bifunctional catalyst is low, which will cause the catalyst to have relatively poor stability; while when the temperature of the hydrothermal reaction is high, the generated nickel-molybdenum precursor is easy to agglomerate and fall off from the foam nickel substrate, resulting in reduced stability of the synthesized nickel-molybdenum precursor and relatively poor catalytic activity.

[0107] Test Example 6

[0108] The electrochemical UOR performance of the MoO2-Ni / NF catalyst prepared in Example 3 was tested using a CHI-660E electrochemical workstation. Urea was added to a 1.0M KOH solution to prepare urea solutions with different concentration gradients (wherein the concentrations of urea were 0.01, 0.02, 0.05, 0.1, 0.5, and 1 mol / L, respectively) as the electrolyte, Ag / AgCl as the reference electrode, the counter electrode as a carbon rod, and the bifunctional catalyst prepared in Example 3 as the working electrode. The UOR polarization curves obtained at different urea concentrations are shown in Figure 1. Figure 6 As shown in the figure, with the increase of urea concentration, the urea oxidation performance of the catalyst improves.

[0109] Test Example 7

[0110] The electrochemical HER performance of the MoO2-Ni / NF catalyst prepared in Example 3 and the Pt / C / NF catalyst prepared in Comparative Example 3 was tested using a CHI-660E electrochemical workstation. 0.5 mol / L urea was added to a 1.0 M KOH solution as an electrolyte, Hg / HgO was used as a reference electrode, a carbon rod was used as a counter electrode, and the MoO2-Ni / NF catalyst and the Pt / C / NF catalyst were used as working electrodes, respectively. The electrochemical HER test was performed using the same three-electrode structure. The HER polarization curves obtained are shown in Figure 2. Figure 7 As shown in the figure, "Mo / NF-HER means that the electrolyte does not contain urea, and Mo / NF-urea-HER means that the electrolyte contains urea". Because urea has no selectivity for HER reaction, the performance of the electrolyte with or without urea is not much different in the HER curve. The MoO2-Ni / NF catalyst in Example 3 is -10mA / cm 2 The performance is -183mV, which is not much lower than that of comparative example 3 using precious metals.

[0111] Test Case 8

[0112] Using a CHI-660E electrochemical workstation, the MoO2-Ni / NF catalyst prepared in Example 3, the RuO2 / NF catalyst prepared in Comparative Example 2, and the nickel foam (denoted as Bare NF) from which the surface nickel oxide was removed according to the method in Example 3 were tested for electrochemical UOR performance. 0.5 mol / L urea was added to a 1.0 M KOH solution as an electrolyte, Ag / AgCl was used as a reference electrode, and a carbon rod was used as a counter electrode. The MoO2-Ni / NF catalyst, RuO2 / NF catalyst, and Bare NF were used as working electrodes, respectively, to perform an electrochemical UOR test. The obtained UOR polarization curves, Tafel slopes, impedances, and electrochemically active surface areas are shown in Figure 2. Figure 8 As shown. In the urea oxidation reaction of MoO2-Ni / NF catalyst, RuO2 / NF catalyst, and Bare NF containing 0.5M urea solution, the curves are as follows Figure 8 This bifunctional catalyst has a current density of 10 mA / cm at 1.383 V (the theoretical voltage required for urea oxidation reaction). 2 It exhibits excellent urea oxidation performance. Figure 8 It can be seen that the overpotential in the polarization curve of MoO2-Ni / NF material is 133mV@10mA / cm 2 Compared with the electrolytic alkaline solution, the reaction is 289mV ahead, and the Tafel slope is the smallest, which is 18mV / dec, the impedance is the smallest, and the electrochemical active surface area is the largest. The UOR performance is better than that of RuO2 / NF and blank nickel foam.

[0113] Test Example 9

[0114] The MoO2-Ni / NF catalyst prepared in Example 3 was tested for its electrochemical UOR seawater performance using a CHI-660E electrochemical workstation. Seawater and an aqueous solution containing 1.0M KOH and 0.5mol / L urea (urea lye) were used as electrolytes, Ag / AgCl was used as the reference electrode, the counter electrode was a carbon rod, and the MoO2-Ni / NF catalyst was used as the working electrode. The UOR seawater electrochemical test was performed using a three-electrode structure. The polarization curve of the UOR seawater is shown in Figure 1. Fig. 9 As shown in the figure, "Mo / NF-400N2-UOR" means that urea alkali solution is used as the electrolyte, and "Mo / NF-400N2-UOR-NaCl" means that seawater is used as the electrolyte. Fig. 9 It can be seen that the material in Example 3 maintains consistent performance in urea alkali solution and seawater, indicating that the prepared bifunctional catalyst MoO2-Ni / NF is suitable for the extreme environment of seawater and has a wider application scenario.

[0115] Test Example 10

[0116] The MoO2-Ni / NF catalyst prepared in Example 3, the RuO2 / NF catalyst prepared in Comparative Example 2, and the Pt / C / NF catalyst prepared in Comparative Example 3 were tested for their full hydrolysis performance using a CHI-660E electrochemical workstation. Using 1.0M KOH solution or adding 0.5 mol / L urea to a 1.0M KOH solution as the electrolyte, the experimental group used MoO2-Ni / NF as the cathode and anode, and the control group used RuO2 / NF and Pt / C / NF as the cathode and anode, respectively. When 1.0M KOH solution (denoted as "HER|OER") and 1.0M KOH solution containing 0.5 mol / L urea (denoted as "HER|UOR") were used as the electrolyte, the polarization curves of the electrolysis of water in the experimental group are as follows: Fig.10 (A) shows that the current density is 100 mA / cm 2 When urea was used as the starting potential, the urea oxidation potential was 1.744 V, which was 176 mV earlier than that of the electrolysis of alkaline solution. The polarization curves of the MoO2-Ni / NF catalyst (i.e. the experimental group, denoted as "Mo / NF|Mo / NF") and the noble metal catalyst (i.e. the control group, denoted as "Pt / C / NF|RuO2 / NF") under the assistance of urea for the complete water splitting are shown in Figure 2. Fig.10 As shown in (B), the voltage of the water electrolysis device constructed with the materials in Example 3 is close to that of the precious metal control group.

[0117] Test Example 11

[0118] The hydrogen production of the MoO2-Ni / NF catalyst prepared in Example 3 was tested using a CHI-660E electrochemical workstation and a gas chromatograph. 0.5 mol / L urea was added to a 1.0 M KOH solution as an electrolyte, and MoO2-Ni / NF was used as the cathode and anode. Nitrogen was first introduced into the assembled device to eliminate the influence of the gas in the water. The device was then sealed to ensure that there was no leakage during the test. The electrochemical workstation was set to the it program, and different voltages were set to run stably for 120 seconds. The collected gas was injected into the gas chromatograph with an injection needle, and the actual hydrogen production at the corresponding voltage was calculated. The Faraday efficiency is the ratio of the molar amount of gas actually produced to the molar amount of gas produced by the theoretical charge. Fig.11 As shown, the hydrogen production increases with the increase of voltage, and the Faraday efficiency is stable at around 70%, which may be caused by the poor sealing of the device.

[0119] Test Example 12

[0120] The MoO2-Ni / NF catalyst prepared in Example 3 was tested for stability in urea solution using a CHI-660E electrochemical workstation. 0.5 mol / L urea was added to a 1.0 M KOH solution as the electrolyte, MoO2-Ni / NF was used as the anode, Ag / AgCl was used as the reference electrode, and the carbon rod was used as the counter electrode. The device was run for 30 h, and new urea solution was replaced every 10 h. The current-time parameters of water electrolysis are shown in Figure 2. Fig.12 As shown, the curve shows a downward trend after running for a period of time, but the performance is restored after replacing new urea alkali solution, indicating that the decline in the curve is caused by the consumption of urea in the solution.

[0121] Test Example 13

[0122] The MoO2-Ni / NF catalyst prepared in Example 3 was tested by in-situ infrared test using a CHI-660E electrochemical workstation and an in-situ infrared instrument. 0.5 mol / L urea was added to a 1.0 M KOH solution as an electrolyte, MoO2-Ni / NF was used as an anode, Ag / AgCl was used as a reference electrode, and a carbon rod was used as a counter electrode. The electrochemical workstation was set to the it program, and different voltages were set to run stably for 300 seconds. At the same time, the in-situ infrared tester was run to monitor in real time the intermediate products and final products generated by different voltages in the catalyst oxidation urea solution. The test results are shown in the figure. Fig.13 As shown, 1750cm -1 The peak intensity increases, and this peak is the δH2O vibration.

[0123] Test Case 14

[0124] The electrochemical UOR and OER performance tests were performed on the catalysts prepared in Example 3 and Comparative Example 4 using a CHI-660E electrochemical workstation. The OER performance was tested in a 1.0M KOH solution, and the UOR performance was tested in a 0.5mol / L urea lye solution. Ag / AgCl was used as the reference electrode, the counter electrode was a carbon rod, and the bifunctional catalysts prepared in Example 3 and Comparative Example 4 were used as the working electrode. The polarization curves of the catalysts with and without an external nickel source were obtained as shown in FIG. Fig.14 Under the same preparation and testing conditions, nickel nitrate was added as a nickel source in the hydrothermal process (i.e., Comparative Example 4). The performance of the catalyst obtained by the test was almost the same as that of the material in Example 3, and the catalyst surface turned yellow-green, indicating that the external nickel source did not work.

[0125] Test Example 15

[0126] The electrochemical UOR and OER performance tests were performed on the catalysts prepared in Example 3 and Comparative Example 5 using a CHI-660E electrochemical workstation. The OER performance was tested in a 1.0M KOH solution, and the UOR performance was tested in a 0.5mol / L urea lye solution. Ag / AgCl was used as the reference electrode, the counter electrode was a carbon rod, and the catalysts prepared in Example 3 and Comparative Example 5 were used as the working electrode. The polarization curves of catalysts on different substrates were obtained as shown in FIG. Fig.15 The nickel foam substrate was replaced with carbon cloth (Comparative Example 5), and the same operation was adopted. The catalyst obtained by the test had almost no urea electrolysis performance, proving that the nickel foam not only served as a substrate, but also precipitated nickel in situ to participate in the electrolysis of urea solution.

[0127] Test Case 16

[0128] The bifunctional catalyst prepared in Example 3 and its precursor obtained in the preparation process were used as test objects, and the structure and composition analysis were carried out as follows:

[0129] (1) The catalyst was cut into 0.5 cm × 0.5 cm size and placed on a glass slide. The XRD pattern was obtained using Shimadzu LabX-XRD-6000 with a diffraction angle of 20-80°. Fig.16 shown. Fig.14 Three strong peaks are shown for the nickel foam substrate, and the remaining peaks correspond to the diffraction peaks of MoO2.

[0130] (2) The catalyst was cut into a size of 0.5 cm × 0.5 cm and tested using an X-ray photoelectron spectrometer with a full spectrum scan energy of 150 eV and a narrow spectrum scan energy of 50 eV; after the electrochemical UOR performance test of Test Example 8, X-ray photoelectron spectroscopy analysis was performed again. The XPS graphs before and after the electrochemical UOR performance test are shown in Figure 2. Fig.17 As shown. Fig.17 It can be seen that before the electrochemical UOR performance test, the valence state of the element Ni is mainly Ni 2+ There is a small amount of Ni 3+ ; The valence state of element Mo is mainly Mo 4+ 、Mo 6+ The element oxygen exists in the form of lattice oxygen, oxygen in water and metal oxygen. After the UOR test, the element Ni valence shifted and moved towards the direction of high binding energy. 2+ 、Ni 3+ The content increases; the valence state of element Mo is Mo 4+ Existence, Mo 6+ The binding energy is reduced, and the valence state of the element oxygen is partially shifted. This indicates that in the urea oxidation mechanism, the main active sites are Ni, Mo 6+ The presence of Ni 3+Oxidation of urea accelerates the oxidation of urea.

[0131] (3) The precursor and bifunctional catalyst were analyzed by laser confocal Raman spectroscopy with an excitation wavelength of 532 nm and a test wavenumber range of 50-3400 cm -1 , the test results are as follows Fig.18 As shown in the Raman spectrum of the nickel-molybdenum oxide precursor, 349 cm -1 and 798.3cm -1 Corresponding Mo-O bending stretch, 519.4cm -1 Corresponding to Ni-O bond, 967.6 cm -1 Corresponding to the symmetric and asymmetric stretching of Mo=O; in the Raman spectrum of nickel molybdenum oxide, 356cm -1 and 750cm -1 Corresponding Mo-O bending stretch, 827.2cm -1 、876.7cm -1 、938.9cm -1 Corresponding to Mo-O-Ni bond.

[0132] Finally, it should be noted that the above examples are only specific embodiments of the present invention. Obviously, the present invention is not limited to the above examples, and many variations are possible. All variations that can be directly derived or associated with the content disclosed by a person skilled in the art should be considered as the protection scope of the present invention.

Claims

1. A method for preparing a bifunctional catalyst for electrochemical hydrogen evolution reaction and urea electrocatalytic oxidation reaction, characterized in that: The following steps are involved: (1) soaking a nickel substrate in an ammonium molybdate solution and stirring the solution, and then performing a hydrothermal reaction at 100-120° C. to separate a product and obtain a precursor; the nickel substrate is foamed nickel; and the concentration of the ammonium molybdate solution is 0.013-0.017 g / mL; (2) Calcining the precursor in a nitrogen atmosphere to obtain a bifunctional catalyst; the bifunctional catalyst includes a nickel substrate and a nickel-molybdenum oxide active material supported on the nickel substrate; the nickel-molybdenum oxide contains a Mo-O-Ni bond; the nickel-molybdenum oxide contains divalent nickel, tetravalent molybdenum and / or hexavalent molybdenum; and the calcination temperature is 300-500°C.

2. The preparation method according to claim 1, characterized in that In step (2), trivalent nickel is also present in the nickel-molybdenum oxide.

3. The preparation method according to claim 1, characterized in that: Prior to step (1), the nickel substrate is pretreated to remove nickel oxide on the surface.

4. The preparation method according to claim 1, characterized in that: In step (1), the hydrothermal reaction time is 5-7 hours.

5. A bifunctional catalyst prepared by the preparation method as claimed in any one of claims 1 to 4.

6. Use of the bifunctional catalyst as claimed in claim 5 in electrochemical hydrogen evolution reaction or urea electrocatalytic oxidation reaction.